Aspek Hukum Pemanfaatan Hutan Lindung Untuk Tempat Wisata - Budi, Fenny; Subekti, Rahayu (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The objective of research was to find out the suitability of the use of protected forests in Karanganyar Regency for tourist attractions with statutory and concerning the legality of retribution withdrawal by local governments which is legal because local governments have regional autonomy.With the legal issue, the author uses normative research methods with perspective research of used cases and regulatory approaches. Nature tourism is one form of protected forests utilization that falls into the group of environmental services utilization according to Article 1 number (6) Regulation of Minister of Forestry Number P.47/MENHUT-II/2013. The helding of tourism in protected forest areas is allowed with the provision not to reduce, change, or eliminate its main functions, change the landscape, and damage environmental elements. However, in the implementation, the parties that involved didn't apply it as it used to be, there were persons who violated the rules that have been made. In addition to violations in the use of protected forests as tourist attractions, other problems occurred was the withdrawal of the retribution, in interviews that the author did with the management of protected forests, it claimed that the withdrawal of retribution in tourist attractions that use protected forests is basically not the right of the local government because the manager of the protected forest doesn't come from the local government but Perum Perhutani instead.